Can dairy help solve the malnutrition crisis in developing countries? An economic analysis - Headey, Derek D. (Oxford University Press, 2023)
Agricultural policies are increasingly being asked to do more to address the extensive global burden of undernutrition (Ruel and Alderman, 2013). Undernutrition in early childhood is particularly costly because of its lifelong consequences: poor health, inferior educational outcomes, and lower wages and productivity in adulthood (Black et al., 2013). But to be effective, nutrition-smart agricultural interventions need to produce meaningful dietary improvements very early in life when economically disadvantaged infants and young children are exposed to rising nutrient requirements that are not met by adequate nutrient intake, absorption, and utilization. The intake problem stems from low-quality diets and poor feeding practices, while absorption and utilization problems arise from repeated as well as chronic infections, particularly of the gut. One area within agriculture with tremendous potential to influence early childhood nutrition is the dairy sector. Dairy products have a range of nutritional and physical characteristics that make them an almost ideal complementary food. Undernourished children in poor countries are often deficient in foods rich in high-quality proteins comprised of essential amino acids that constitute the building blocks for linear growth and cognitive development (Semba, 2016). Dairy has a higher digestibility-corrected amino acid score than any other food (1.21) and is particularly efficacious at closing amino acid gaps in the monotonous diets prevalent in Africa and Asia (FAO, 2013), and in poorer populations more exposed to infections (Semba, 2016). Dairy is unique in stimulating plasma insulin-like growth factor 1 (IGF-1), a growth hormone that acts to increase the uptake of amino acids (FAO, 2013). Dairy is also dense in calories, fat, and various micronutrients (vitamin A and B12), as well as being exceptionally rich in calcium (which contributes to bone length and strength), potassium, magnesium, and phosphorus (Dror and Allen, 2014). Finally, the sheer density of multiple macro- and micronutrients in dairy products—as well as their taste, and familiar texture and consistency—makes them almost ideal for infants and young children with small stomachs incapable of consuming large quantities of nutrient-sparse foods so common in diets of poorer households.